Computational Studies on Optoelectronic and Nonlinear Properties of Octaphyrin Derivatives - Islam, Nasarul; Lone, Irfan H. (Frontiers in Chemistry, 2017)
The electronic and nonlinear optical properties of octaphyrin derivatives were studied by employing the DFT/TDFT at CAM-B3LYP/6-311++G (2d, 2p) level of the theory. Thiophene, phenyl, methyl and cyano moieties were substituted on the molecular framework of octaphyrin core, in order to observe the change in optoelectronic and nonlinear response of these systems. The frontier molecular orbital studies and values of electron affinity reveals that the studied compounds are stable against the oxygen and moisture present in air. The calculated ionisation energies, adiabatic electron affinity and reorganization energy values indicate that octaphyrin derivatives can be employed as effective n-type material for Organic Light Emitting Diodes (OLEDs). This character shows an enhancement with the introduction of an electron withdrawing group in the octaphyrin framework. The polarizability and hyperpolarizability values of octaphyrin derivatives demonstrate that they are good candidates for nonlinear optical devices. The nonlinear response of these systems shows enhancement on the introduction of electron donating groups on octaphyrin moiety. However these claims needs further experimental verification.